FORUM on M.M. Merritt, Cambridge Elements: The Philosophy of Immanuel Kant. The Sublime: with M. M. Merritt, D. Ainslie, L. Filieri, P. Guyer, S. Matherne, R. Zuckert (Lebenswelt. Aesthetics and philosophy of experience., 2023)
...